DESIGN AND NUMERICAL SIMULATION OF FRANCIS REVERSIBLE PUMP-TURBINE AT UPPER CISOKAN PUMPED STORAGE - Zharfan Sambas, Rizqy
In order to achieve Net Zero Emission in 2060, Indonesia Government have planned several strategy to reduce carbon emission. One of the strategy is to provide 23% electricity demand from renewable energy sources by 2025. Development of solar and wind power plant already conducted. The drawbacks of development this kind of power plant is intermittent. This intermittent problem cause instability in PLN grid. Thus, energy storage is required to support this problem. One type of energy storage that suitable for large scale application is Pumped Hydro Energy Storage or PHES. This energy storage consist of turbine and pump. Currently Indonesia Government are constructing the first PHES in Indonesia located at Cisokan, West Java with generating capacity of 1 GW. Reversible Pump-Turbine is used as main component to generate electricity and also pumping fluid. In this research, the design of RPT will be conducted including design of spiral casing, guide vane, and draft tube. Firstly, the geometry and model will be designed using Vista CPD, BladeGen, and Solidworks. Next step is perform numerical simulation using Ansys Fluent. Simulation will be conducted in steady condition with variance of guide vane opening angle and turbine outlet boundary condition. By maintaining inlet fluid boundary condition and rotational speed at 333 rpm, highest turbine efficiency achieved at 79% with 292 MW mechanical power generated. Meanwhile, highest pumping efficiency achieved at 76,8% with 279 m head produced at 86,5 m3/s. Both highest efficiency point are based on 34o guide vane opening angle. Based on pressure contour, cavitation are happened locally at the same location (runner/impeller blade) while RPT perform as turbine and pump.